The effect of GLP-1 receptor agonists on N-terminal pro-brain natriuretic peptide. A scoping review and metanalysis. (15th June 2022) - Avogaro, Angelo; Azzolina, Danila; Gregori, Dario; De Kreutzenberg, Saula; Fadini, Gian Paolo; Mannucci, Edoardo
Abstract: Aims: Glucagon-like peptide 1 receptor agonists (GLP-1RA) decrease the risk of major adverse cardiovascular events (MACE). However, their influence on the risk of heart failure (HHF) hospitalization is marginal, which is unexpected given their benefits on cardiometabolic risk, especially on bodyweight reduction. This meta-analysis aimed to map the effects of GLP-1RA on N-terminal pro-BNP. Methods and results: We retrieved from a Medline and Embase all randomized trials comparing GLP-1RA with placebo, reporting NT-proBNP concentrations. The primary outcome was the change in N-terminal pro-BNP values from baseline to end-of-treatment with GLP-1RA versus placebo (reported as standard deviations, SD). We included nine trials (543 patients in active treatment and 536 in placebo). We observed significantly greater reductions in N-terminal pro-BNP with GLP-1RA versus placebo (−0.14 SD; 95% CI −0.27; −0.01; p = 0.03). Upon meta-regression, no modifying effect of age, HbA1c, and body mass index were observed, nor was any meta-correlation between the change in NT-proBNP and the change in HbA1c or body weight. Conclusions: GLP-1RA can significantly decrease N-terminal pro-BNP. This effect was independent of baseline age, body weight, and metabolic control. Highlights: Glucagon-like peptide 1 receptor agonists (GLP-1RA) decrease the risk of major adverse cardiovascular events We observed significantly reductions in N-terminal pro-BNP with GLP-1RA versus placebo. Upon meta-regression, no modifying effect of age, HbA1c, and body mass index was observed, nor there was any meta-correlation between the change in NT-proBNP according to these parameters. GLP-1RA can significantly decrease N-terminal pro-BNP